Customer engagement in a Big Data world. Issue 2 (10th April 2017) - Kunz, Werner; Aksoy, Lerzan; Bart, Yakov; Heinonen, Kristina; Kabadayi, Sertan; Ordenes, Francisco Villarroel; Sigala, Marianna; Diaz, David; Theodoulidis, Babis
Abstract : Purpose: This paper aims to propose that the literature on customer engagement has emphasized the benefits of customer engagement to the firm and, to a large extent, ignored the customers' perspective. By drawing upon co-creation and other literature, this paper attempts to alleviate this gap by proposing a strategic framework that aligns both the customer and firm perspectives in successfully creating engagement that generates value for both the customer and the bottom line. Design/methodology/approach: A strategic framework is proposed that includes the necessary firm resources, data, process, timeline and goals for engagement, and captures customers' motives, situational factors and preferred engagement styles. Findings: The authors argue that sustainability of data-driven customer engagement requires a dynamic and iterative value generation process involving customers recognizing the value of engagement behaviours and firm's ability to capture and passing value back to customers. Originality/value: This paper proposes a dynamic strategic value-creation framework that comprehensively captures both the customer and firm perspectives to data-driven customer engagement.